2012
DOI: 10.1111/j.1365-2141.2011.09011.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the elderly patient with diffuse large B cell lymphoma

Abstract: SummaryThe majority of patients with diffuse large B-cell lymphoma are over the age of 60 years and the management of these patients is often sub-optimal. Intensive therapy with curative intent should be given to all patients who can tolerate such therapy, and this requires very careful evaluation of each patient prior to treatment allocation. A detailed history and examination are required, with attention to concomitant disease and existing drug therapy. A quantitative assessment of comorbidity and a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 92 publications
(105 reference statements)
2
44
0
1
Order By: Relevance
“…1,2 Although differences in tumor biology may play a partial role, 3 the management of these patients is heavily influenced by their preexisting comorbidities and a variety of geriatric syndromes such as polypharmacy, risk of falling, depression, cognitive impairment, sarcopenia, and frailty. 4,5 Compounding these challenges is the lack of randomized data to determine the risk-to-benefit ratio of different types of therapy and to guide treatment decision-making, because elderly patients are generally excluded from pivotal drug trials. 6 The current gold standard for treating elderly patients with DLBCL was established by the Groupe d'Etude des Lymphomes de l'Adulte (GELA) non-Hodgkin lymphoma trial (GELA LNH-98-5), which showed that the addition of rituximab to 8 cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) chemotherapy improved the long-term survival outcome for patients 60 to 80 years old.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although differences in tumor biology may play a partial role, 3 the management of these patients is heavily influenced by their preexisting comorbidities and a variety of geriatric syndromes such as polypharmacy, risk of falling, depression, cognitive impairment, sarcopenia, and frailty. 4,5 Compounding these challenges is the lack of randomized data to determine the risk-to-benefit ratio of different types of therapy and to guide treatment decision-making, because elderly patients are generally excluded from pivotal drug trials. 6 The current gold standard for treating elderly patients with DLBCL was established by the Groupe d'Etude des Lymphomes de l'Adulte (GELA) non-Hodgkin lymphoma trial (GELA LNH-98-5), which showed that the addition of rituximab to 8 cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) chemotherapy improved the long-term survival outcome for patients 60 to 80 years old.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of elderly is still a matter of debate in oncology. In patients with lymphoma the age limit more frequently used to discriminate between younger and older patients is 65 [2].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these patients are over the age of 60 years and the steady improvement of life expectancy will probably further increase their number in the future [2]. Therefore, trying to improve the survival of this category of patients represents one of the major challenges for the haematologists.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although treatment with an ACR is associated with improved response rates and progression-free survival (PFS) in elderly patients compared with non-ACR treatment, the associated toxicities including myelosuppression, febrile neutropenia, mucositis, and cardiomyopathy might exclude many elderly patients from such aggressive treatment. 8,10 We performed a retrospective cohort analysis of patients with DLBCL aged ≥65 years at diagnosis treated with either an ACR or a non-ACR to examine clinical factors that led to treatment selection and assess toxicity and outcomes for a population of DLBCL that was comparable to SEER–Medicare studies but included clinical data suitable for detailed exploration of anthracycline effects on cardiac function and treatment modification.…”
Section: Introductionmentioning
confidence: 99%